Peningkatan Kemampuan Motorik Halus Anak melalui Bermain Oobleck - Mufid, Abdul; Mukaromah, Sayyidatul; Lestari, Puji (Institut Agama Islam Sunan Giri Ponorogo, 2022)
Children's motor skills greatly affect the strength and mental development of a child, because with good facilities from the role of parents or people around, this can increase the child's confidence and ability to coordinate hand muscle movements, eye nerves in doing something. This study aims to describe how the implementation of the oobleck game and what changes are seen after the children play the oobleck game. This study uses a qualitative research approach with a descriptive type of research. This study uses research subjects at KB Pelangi Ceria Blora, using data collection such as observations, interviews, and also documentation. As for what is studied in this study, how to improve the fine motor skills of children in KB Pelangi Ceria Blora by playing oobleck, where this game really attracts children's attention and becomes children's enthusiasm to participate in it. With the oobleck game that is done repeatedly, it will be seen a comparison of the improvement in the fine motor skills of the child.